THE RELATIONSHIP BETWEEN THE INTENSITY OF TAHAJJUD PRAYER AND BLOOD PRESSURE IN THE ELDERLY AT THE KARANG WERDA COMMUNICATION FORUM IN JEMBER REGENCY - Sofiana, Kristianningrum Dian; Salshabilla, Dinda Syahva; Hamzah, Zahreni; Wulandari, Pipiet; Firdaus, Jauhar; Sholeh, Moh; kristianningrum dian (Jurnal Penelitian, 2025)
The aging process is a phase in which the body's ability to repair and regenerate itself gradually declines, which can lead to increased stiffness of blood vessels and higher blood pressure. Hypertension is a condition where blood pressure exceeds 140 mmHg systolic and more than 90 mmHg diastolic. This condition can be caused by mental conditions that influence people's stress levels. Managing blood pressure issues in the elderly can be achieved through meditation, such as performing the Tahajjud prayer. The Tahajjud prayer is thought to aid in stress reduction and contribute to lowering blood pressure. The purpose of this study is to investigate the relationship between the intensity of Tahajjud prayer and blood pressure in elderly individuals at the elderly forum in Jember Regency. This is a cross-sectional study that included a total sample of 189 elderly individuals. The prevalence of hypertension is 59.3%, 55% of them have already performed the Tahajjud prayer, and 45% do not perform the Tahajjud prayer. A significant relationship exists between the intensity of Tahajjud prayer and blood pressure in the elderly population of Jember Regency.